The heretic royal eaudiobook - Aiken, G.A (Recorded Books, Inc., 2022)
In the G.A. Aiken's fantasy follow up to the USA Today bestselling Scarred Earth Saga's The Princess Knight and The Blacksmith Queen, two sisters battle for a single throne, warring factions take up arms, a land is divided, and uncertain allies become very certain lovers ... With subtle commentary on today's political polarization, this riveting epic celebrates strong female characters and champions the underdog within a diverse, high fantasy framework. As two sisters battle for a single throne in G.A. Aiken's newest fantasy, warring factions take up arms, a land is divided, and uncertain allies become very certain lovers ... GODS SAVE THE QUEEN! Ainsley Farmerson has always planned to break free of the family business—and the family drama. But what was once farming, smithworking, and bickering over the dinner table has turned into open warfare between sisters. Sides have been taken, lives are on the line, and Ainsley has no doubt which sister must be queen. She'll do whatever is necessary to take down the soulless Beatrix. Even if that means joining forces with angry battle nuns, irritating monks, and overbearing centaurs. Gruffyn of the Torn Moon Clan has no time for human beings. And yet ... there is something about the uncontrollable princess that he can't ignore. Maybe it's the way her eldest sisters underestimate her. Or her bravery facing down dragons and mad queens from distant lands. Whatever the reason, Gruff is willing to fight by this human's side. Not only for the entertainment value, but because she's right. Beatrix must never be queen. So whatever he has to do, whoever he has to destroy, Gruff will battle beside Ainsley. Fast. Hard. And with absolutely no mercy ...